國民小學教師海洋教育能力指標及權重體系建構之研究 Construction of Competence Indicators and Weight System of Marine Education for Elementary School Teachers - 許籐繼 Terng-Ji Sheu (National Taiwan Normal University, 2011)
本研究旨在建構國民小學教師海洋教育能力指標及權重體系，為達成前述之目的，採用專家座談（panel discussion）、德懷術（Delphi technique）、層級分析（analytic hierarchy process,AHP）等方法。專家座談邀請11位專家，討論與修正指標初稿。其次，邀請18位德懷術專家成員，進行多回合的問卷調查，直到達成共識為止。第三，根據所形成的能力指標設計相對權重調查問卷，針對18位專家進行指標相對權重的調查。主要研究發現有二：一、完成國民小學教師海洋教育能力指標之建構，共計四層面十二向度與四十一細項指標；二、建立四層面十二向度與四十一細項指標之相對權重體系。最後，據以提出研究結論和建議，供實施海洋教育相關機構、人員和未來進一步研究之參考。 The purpose of this study was to construct the competence indicators and a weight system for teachers implementing marine education into elementary schools. To achieve this, the methods adopted were panel discussion, the Delphi technique, and analytic hierarchy process (AHP). The results were as follows: 1. Complete constructing the competence indicators of the teachers' implementing marine education in elementary schools, including 4 dimensions, 12 items, and 41 indicators; and 2. create the relative weight system of 4 dimensions, 12 items, and 41 indicators. Lastly, the suggestions and conclusions from the results were provided for the relative staff and institution implementing marine education, and for future studies.